A quadruple-reversible shape memory co-crystallized polyurethane and its preparation method and application
By preparing quadruple-reversible shape memory co-crystalline polyurethane under high solvent content, cross-linking with a click reaction of poly(ε-caprolactone) compounds and trithiol cross-linking agent, and co-crystallization of PCL and PPDL, the problem of poor temperature resistance of PCL/PPDL reversible shape memory system was solved, and the improvement of quadruple-shaped memory performance was achieved.
Patent Information
- Application Number
- CN202211552717.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-06
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-12-06
AI Technical Summary
The existing PCL/PPDL reversible shape memory system has the problem of poor temperature resistance, making it difficult to achieve quadruple shape memory performance.
By preparing quadruple-reversible shape memory co-crystalline polyurethane under high solvent content, poly(ε-caprolactone) compounds and trithiol crosslinking agent are used to perform click reaction crosslinking under ultraviolet light to form a polymer network, and the nanomechanical properties of the material are improved through co-crystallization of PCL and PPDL.
It significantly enhances the temperature resistance of bidirectional shape memory performance and realizes quadruple shape memory performance, so that the application performance of materials in intelligent control, biomedical intelligent materials and soft robots can be improved.
Smart Images

Figure CN115819694B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of shape memory materials, and in particular to a quadruple-reversible shape memory co-crystallized polyurethane and a preparation method and application thereof. Background Art
[0002] Thermally triggered reversible shape memory polymers have become a research hotspot in the field of smart materials due to their easy design and controllability in achieving reversible shape changes. In recent years, researchers have achieved reversible shape memory effects using strategies such as laminated polymers, liquid crystal elastomers, and semi-crystalline polymers. Among them, strategies based on semi-crystalline polymers have been widely developed due to their simplicity of synthesis (compared to liquid crystal elastomers) and ease of reprogramming shape changes (compared to laminated polymers and liquid crystal elastomers). Based on the existing reversible shape memory system, it is a challenge to improve its performance while achieving multiple shape memory properties.
[0003] Bio-based PCL (poly (ε-caprolactone)) and PPDL (poly (ω-pentadecalactone)) are bio-based polyesters and are considered green materials. They are expected to replace some traditional fossil-based polymer materials in packaging, agriculture, textiles and biomedical materials. The semi-crystalline bidirectional shape memory polymer first realized by Andreas Lendlein's research group is composed of PCL and PPDL (Behl, M., Kratz, K., Zotzmann, J., U. and Lendlein, A. (2013), Reversible Bidirectional Shape-Memory Polymers. Adv. Mater., 25: 4466-4469.). Song et al. (Song, H.; Fang, Z.; Jin, B.; Pan, P.; Zhao, Q.; Xie, T., Synergetic Chemical and Physical Programming for Reversible Shape Memory Effect in a Dynamic Covalent Network with Two Crystalline Phases. ACS Macro Letters 2019, 8 (6), 682-686.) PCL / PPDL polyurethane materials prepared by photocuring process also have bidirectional shape memory properties, and also pointed out that the reversible shape memory properties of this system are easily affected by temperature. While reversible shape memory is realized, the realization of multiple shape memory properties makes the material have more complex shape memory properties, which is better suitable for applications in various fields, but there are few reports at present. However, the current PCL / PPDL reversible shape memory system has the problem of poor temperature resistance, and the improvement of its two-way shape memory material performance and the realization of diversified shape memory performance (quadruple shape memory) still face huge challenges. Summary of the invention
[0004] The purpose of the present invention is to provide a quadruple-reversible shape memory co-crystallized polyurethane and a preparation method and application thereof, which can significantly enhance the temperature resistance of the two-way shape memory performance and also achieve quadruple shape memory performance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a quadruple-reversible shape memory co-crystallized polyurethane, comprising the following steps:
[0007] The method comprises mixing poly(ω-pentadecalactone) diallylformamide, a double-bond-terminated poly(ε-caprolactone) compound, a trithiol crosslinking agent, a photoinitiator and an organic solvent, photocuring the obtained mixed system, and removing the solvent to obtain a quadruple-reversible shape memory co-crystalline polyurethane; wherein the mass fraction of the organic solvent in the mixed system is 85-92wt%;
[0008] The double-bond terminated poly(ε-caprolactone) compounds include poly(ε-caprolactone) diallylformamide or poly(ε-caprolactone) diacrylate.
[0009] Preferably, the preparation method of the poly(ω-pentadecalactone) diallylformamide comprises the following steps:
[0010] Poly(ω-pentadecalactone) diol, allyl isocyanate, a catalyst and a first solvent are mixed to carry out a first addition reaction to obtain poly(ω-pentadecalactone) diallylformamide; the molar ratio of the poly(ω-pentadecalactone) diol to allyl isocyanate is 1:(2-3); the catalyst is dibutyltin dilaurate, and the mass of the catalyst is 1-4% of the mass of the poly(ω-pentadecalactone) diol; the temperature of the first addition reaction is 85-95°C, and the time is 5h.
[0011] Preferably, the preparation method of the poly(ω-pentadecalactone) diol comprises the following steps:
[0012] 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 1,8-octanediol and ω-pentadecalactone are mixed, and the obtained mixture is subjected to a ring-opening polymerization reaction to obtain poly(ω-pentadecalactone)diol; the mass of the 1,5,7-triazidobicyclo(4.4.0)dec-5-ene is 1 to 3.5% of the mass of the mixture; the mass of the 1,8-octanediol is 2 to 3.5% of the mass of the mixture; the temperature of the ring-opening polymerization reaction is 100°C and the time is 48 hours.
[0013] Preferably, the preparation method of the poly(ε-caprolactone) diallylformamide comprises the following steps:
[0014] Poly(ε-caprolactone) diol, allyl isocyanate, a catalyst and a second solvent are mixed to carry out a second addition reaction to obtain poly(ε-caprolactone) diallyl formamide; the molar ratio of the poly(ε-caprolactone) diol to allyl isocyanate is 1:(2-3); the catalyst is dibutyltin dilaurate, and the mass of the catalyst is 0.5-2% of the mass of the poly(ε-caprolactone) diol; the temperature of the second addition reaction is 85-95°C and the time is 5h.
[0015] Preferably, the mass of the poly(ω-pentadecalactone) diallylformamide is 5 to 20% of the sum of the masses of the poly(ω-pentadecalactone) diallylformamide and the poly(ε-caprolactone) compound.
[0016] Preferably, the organic solvent includes trichloroethane or chloroform, and the solid content of the mixed system is 8 to 15 wt%; the trithiol crosslinking agent includes trimethylolpropane tris(3-mercaptopropionate); the molar ratio of the thiol group in the trithiol crosslinking agent to the total double bond functional groups in the double-bond terminated poly(ε-caprolactone) compounds and poly(ω-pentadecalactone) diallylformamide) is 3:(2 to 6).
[0017] Preferably, the photoinitiator includes a photoinitiator 651; the mass of the photoinitiator is 1 to 5% of the sum of the masses of the poly(ω-pentadecalactone) diallylformamide and the poly(ε-caprolactone) compounds.
[0018] Preferably, the light curing time is 5 to 10 minutes.
[0019] The present invention provides a quadruple-reversible shape memory co-crystallized polyurethane prepared by the preparation method described in the above technical scheme.
[0020] The present invention provides the application of the quadruple-reversible shape memory co-crystallized polyurethane described in the above technical solution in intelligent control, biomedical intelligent materials or soft robots.
[0021] The invention provides a method for preparing a quadruple-reversible shape memory co-crystallized polyurethane, comprising the following steps: mixing poly(ω-pentadecalactone) diallylformamide, a double-bond-terminated poly(ε-caprolactone) compound, a trithiol crosslinking agent, a photoinitiator and an organic solvent, photocuring the obtained mixed system, and removing the solvent to obtain a quadruple-reversible shape memory co-crystallized polyurethane; the mass fraction of the organic solvent in the mixed system is 85-92wt%; the double-bond-terminated poly(ε-caprolactone) compound comprises poly(ε-caprolactone) diallylformamide or poly(ε-caprolactone) diacrylate.
[0022] The invention prepares polyurethane by rapid photocuring under the condition of high solvent content (85-92wt%), utilizes the double bonds at both ends of poly(ε-caprolactone) compounds and the thiol groups of trithiol crosslinking agent to undergo click reaction under ultraviolet light to form a polymer network, PPDL is more evenly dispersed in PCL under high solvent content, large volume shrinkage during solvent removal after curing causes entanglement of PPDL and PCL chains, and further co-crystallization of PCL and PPDL occurs, and co-crystallization causes the polyurethane system to contain three melting transitions and two crystallization transitions, thereby improving the nanomechanical properties of the polyurethane, enhancing the temperature resistance of the two-way shape memory performance, having a larger reversible elongation strain, and also realizing quadruple shape memory performance, realizing the improvement of the performance of PCL / PPDL-based reversible shape memory polyurethane and multiple shape memory performance, thereby increasing the service temperature, improving the temperature resistance, increasing the reversible strain, and complicating the shape memory properties in the fields of intelligent control, biomedical intelligent materials, soft robots, etc. Among them, the temperature resistance enhancement refers to the shape memory performance of the two-way shape memory co-crystallized polyurethane obtained by curing at a high solvent content with the high temperature trigger temperature (T high ) will not deteriorate dramatically. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1is the infrared image of different substances in Example 1;
[0024] Figure 2 is a DSC curve diagram of the two-way shape memory co-crystalline polyurethane obtained by photocuring at a high solvent content in Example 1;
[0025] Figure 3 The two-way shape memory performance test result of the two-way shape memory co-crystallized polyurethane obtained by photocuring at a high solvent content in Example 1;
[0026] Figure 4 The DSC curve of the bidirectional shape memory polyurethane prepared by curing at a low solvent content in Comparative Example 1;
[0027] Figure 5 The two-way shape memory performance test results of the two-way shape memory polyurethane prepared by curing at a low solvent content in Comparative Example 1;
[0028] Figure 6 This is a quadruple shape memory demonstration diagram of the co-crystallized polyurethane prepared in Example 1. DETAILED DESCRIPTION
[0029] The present invention provides a method for preparing a quadruple-reversible shape memory co-crystallized polyurethane, comprising the following steps:
[0030] The method comprises mixing poly(ω-pentadecalactone) diallylformamide, a double-bond-terminated poly(ε-caprolactone) compound, a trithiol crosslinking agent, a photoinitiator and an organic solvent, photocuring the obtained mixed system, and removing the solvent to obtain a quadruple-reversible shape memory co-crystalline polyurethane; wherein the mass fraction of the organic solvent in the mixed system is 85-92wt%;
[0031] The double-bond terminated poly(ε-caprolactone) compounds include poly(ε-caprolactone) diallylformamide or poly(ε-caprolactone) diacrylate.
[0032] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0033] In the present invention, the preparation method of the poly(ω-pentadecalactone) diallylformamide preferably comprises the following steps:
[0034] The poly(ω-pentadecalactone) diol, allyl isocyanate, a catalyst and a first solvent are mixed and subjected to a first addition reaction to obtain poly(ω-pentadecalactone) diallyl formamide.
[0035] In the present invention, the preparation method of the poly(ω-pentadecalactone) diol preferably comprises the following steps:
[0036] 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 1,8-octanediol and ω-pentadecalactone are mixed, and the obtained mixture is subjected to a ring-opening polymerization reaction to obtain poly(ω-pentadecalactone)diol.
[0037] In the present invention, the mass of the 1,5,7-triazidebicyclo(4.4.0)dec-5-ene (TBD) is preferably 1 to 3.5% of the mass of the mixed material; the mass of the 1,8-octanediol is preferably 2 to 3.5% of the mass of the mixed material, more preferably 3.29%; the mass of the ω-pentadecalactone is preferably 93.58% of the mass of the mixed material.
[0038] The present invention has no special limitation on the mixing of the 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 1,8-octanediol and ω-pentadecalactone, and the materials can be uniformly mixed according to a process well known in the art.
[0039] In the present invention, the temperature of the ring-opening polymerization reaction is preferably 100° C., and the time is preferably 48 hours; the ring-opening polymerization reaction is preferably carried out under stirring conditions. The present invention has no special limitation on the stirring rate, as long as the reaction proceeds smoothly.
[0040] After the ring-opening polymerization reaction is completed, the present invention preferably dissolves the obtained product in excess chloroform, precipitates it in n-hexane, filters it, and dries the obtained precipitate to obtain poly(ω-pentadecalactone) diol; the present invention has no special limitation on the precipitation, filtration and drying processes, and can be carried out according to processes well known in the art.
[0041] In the present invention, the molar ratio of the poly(ω-pentadecalactone) diol to allyl isocyanate is preferably 1:(2-3), more preferably 1:2.5.
[0042] In the present invention, the catalyst is preferably dibutyltin dilaurate (DBTDL), and the mass of the catalyst is preferably 1 to 4% of the mass of the poly(ω-pentadecalactone) diol;
[0043] In the present invention, the first solvent is preferably DMF. The present invention has no particular limitation on the amount of the first solvent used, as long as it can ensure the smooth progress of the reaction.
[0044] The present invention has no particular limitation on the mixing of the poly(ω-pentadecalactone) diol, allyl isocyanate, catalyst and the first solvent. The materials can be uniformly mixed according to a process well known in the art.
[0045] In the present invention, the temperature of the first addition reaction is preferably 85-95°C, more preferably 90°C, and the time is preferably 5h; the first reaction is preferably carried out under nitrogen atmosphere + stirring conditions. The present invention has no special limitation on the stirring, and the reaction can be ensured to proceed smoothly according to the process well known in the art.
[0046] After the first addition reaction is completed, the present invention preferably precipitates the obtained reaction product in n-heptane, washes and dries in sequence to obtain poly(ω-pentadecalactone)diallylformamide. The present invention has no particular limitation on the precipitation, washing and drying, and can be carried out according to processes well known in the art.
[0047] In the present invention, the double-bond terminated poly(ε-caprolactone) compounds include poly(ε-caprolactone) diallylformamide or poly(ε-caprolactone) diacrylate; the poly(ε-caprolactone) diacrylate has Mn=2000 or Mn=3000 and is purchased from AlfaAesar.
[0048] In the present invention, the preparation method of the poly(ε-caprolactone) diallylformamide preferably comprises the following steps:
[0049] The poly(ε-caprolactone) diol, allyl isocyanate, a catalyst and a second solvent are mixed and subjected to a second addition reaction to obtain poly(ε-caprolactone) diallylformamide.
[0050] In the present invention, the molecular weight of the poly(ε-caprolactone) diol (PCL-2OH) is preferably Mn=2000 or Mn=3000; it was purchased from Juren Chemical.
[0051] In the present invention, the molar ratio of the poly(ε-caprolactone) diol to allyl isocyanate is preferably 1:(2-3), more preferably 1:2.5; the catalyst is preferably dibutyltin dilaurate, and the mass of the catalyst is preferably 0.5-2% of the mass of the poly(ε-caprolactone) diol, more preferably 1-1.5%.
[0052] In the present invention, the second solvent is preferably DMF. The present invention has no particular limitation on the amount of the second solvent, as long as it can ensure the smooth progress of the reaction.
[0053] The present invention has no particular limitation on the mixing of the poly(ε-caprolactone) diol, allyl isocyanate, catalyst and second solvent. The materials can be mixed uniformly according to a process well known in the art.
[0054] In the present invention, the temperature of the second addition reaction is preferably 85-95°C, more preferably 90°C, and the time is preferably 5 hours; the second reaction is preferably carried out under a nitrogen atmosphere + stirring conditions. The present invention has no special limitation on the stirring, and the reaction can be ensured to proceed smoothly according to the process well known in the art.
[0055] After the second addition reaction is completed, the present invention preferably precipitates the obtained reaction product in n-heptane, washes and dries it in sequence to obtain poly(ε-caprolactone)diallylformamide. The present invention has no particular limitation on the precipitation, washing and drying, and can be carried out according to processes well known in the art.
[0056] In the present invention, the mass of the poly(ω-pentadecalactone) diallylformamide is preferably 5-20% of the sum of the mass of the poly(ω-pentadecalactone) diallylformamide and the poly(ε-caprolactone) compound, and more preferably 15%.
[0057] In the present invention, the trithiol crosslinking agent includes trimethylolpropane tris(3-mercaptopropionate) (TMPMP); the molar ratio of the thiol group in the trithiol crosslinking agent to the total double bond functional groups in the double-bond terminated poly(ε-caprolactone) compounds and poly(ω-pentadecalactone) diallylformamide) is 3:(2-6).
[0058] In the present invention, the photoinitiator preferably includes photoinitiator 651; the mass of the photoinitiator is preferably 1-5% of the sum of the mass of the poly(ω-pentadecalactone) diallylformamide and the poly(ε-caprolactone) compounds, and more preferably 2%.
[0059] In the present invention, the organic solvent preferably includes trichloroethane or chloroform, and the mass fraction of the organic solvent in the mixed system is 85-92wt%; that is, the solid content of the mixed system is preferably 8-15wt%.
[0060] The present invention has no particular limitation on the mixing of the poly(ω-pentadecalactone) diallylformamide, poly(ε-caprolactone) compounds, trithiol crosslinking agent, photoinitiator and organic solvent, and the materials can be uniformly mixed according to a process well known in the art.
[0061] After the mixing is completed, the present invention pours the obtained mixed system into an open culture dish, and places the open surface under an ultraviolet lamp for light curing; the light curing time is preferably 5 to 10 minutes.
[0062] After the photocuring is completed, the product is preferably desolventized at 50° C. and demolded to obtain the co-crystallized polyurethane. The desolventization and demolding are not particularly limited in the present invention and can be carried out according to processes well known in the art.
[0063] The present invention provides a co-crystallized polyurethane prepared by the preparation method described in the above technical scheme.
[0064] The present invention provides the application of the co-crystallized polyurethane described in the above technical solution in intelligent control, biomedical intelligent materials or soft robots. The present invention has no special limitation on the application method, and the application can be carried out according to methods well known in the art.
[0065] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] Example 1
[0067] 102 g of ω-pentadecalactone, 3.59 g of 1,8-octanediol and 3.41 g of 1,5,7-triazidobicyclo(4.4.0)dec-5-ene were placed in a three-necked flask, connected to a condenser, and magnetically stirred at 100° C. for 48 h. The obtained product was dissolved in excess chloroform, precipitated in n-hexane, filtered and dried to obtain poly(ω-pentadecalactone) diol powder;
[0068] Weigh 8.5 g of the poly(ω-pentadecalactone) diol into a three-necked flask, add 18 g of DMF, 0.78 mL (0.663 g) of allyl isocyanate and 0.3 g of DBTDL, pass nitrogen into a condenser, and react at 90° C. with magnetic stirring for 5 h. The product after the reaction is precipitated in n-heptane, washed and dried to obtain poly(ω-pentadecalactone) diallylformamide;
[0069] Take 20g poly(ε-caprolactone) diol (Mn=3000), 10g DMF, 1.63mL allyl isocyanate and 0.3g DBTDL, add nitrogen into a condenser, react at 90°C with magnetic stirring for 5h, precipitate the reaction product in n-heptane, wash and dry to obtain poly(ε-caprolactone) diallyl formamide;
[0070] 0.3 g of poly (ω-pentadecalactone) diallylformamide, 1.7 g of poly (ε-caprolactone) diallylformamide, 0.2016 g of TMPMP and 0.04 g of photoinitiator 651 were dissolved in 18 g of trichloroethane, the content of the solvent trichloroethane in the mixed system was 90 wt %, that is, the solid content was 10 wt %. The obtained mixed solution was poured into an open culture dish, and the open surface was placed under an ultraviolet lamp for curing for 5 min. The solvent was removed at 50° C. and the mold was released to obtain a bidirectional shape memory co-crystalline polyurethane.
[0071] Example 2
[0072] The only difference from Example 1 is that 20 g of poly(ε-caprolactone) diol (Mn=2000), 10 g of DMF, 1.63 mL of allyl isocyanate and 0.2 g of DBTDL were added to a condenser through nitrogen, and the mixture was stirred with magnetic stirring at 90° C. for 5 h. The reaction product was precipitated in n-heptane, washed and dried to obtain poly(ε-caprolactone) diallylformamide.
[0073] Example 3
[0074] The only difference from Example 1 is that: no poly(ε-caprolactone) diallylformamide and preparation are required;
[0075] 0.3 g of poly (ω-pentadecalactone) diallylformamide, 1.7 g of poly (ε-caprolactone) diacrylate (Mn = 3000), 0.3 g of TMPMP and 0.04 g of photoinitiator 651 were dissolved in 4.67 g of trichloroethane, and the resulting mixed solution was poured into an open culture dish. The open surface was placed under an ultraviolet lamp for curing for 5 min, the solvent was removed at 50°C, and the mold was released to obtain a bidirectional shape memory co-crystalline polyurethane.
[0076] Example 4
[0077] The only difference from Example 1 is that: no poly(ε-caprolactone) diallylformamide and preparation are required;
[0078] 0.3 g of poly (ω-pentadecalactone) diallylformamide, 1.7 g of poly (ε-caprolactone) diacrylate (Mn = 2000), 0.3 g of TMPMP and 0.04 g of photoinitiator 651 were dissolved in 4.67 g of trichloroethane, and the resulting mixed solution was poured into an open culture dish. The open surface was placed under an ultraviolet lamp for curing for 5 min, the solvent was removed at 50°C, and the mold was released to obtain a bidirectional shape memory co-crystalline polyurethane.
[0079] Comparative Example 1
[0080] The only difference from Example 1 is that the content of trichloroethane in the mixed system is 70 wt % (ie, the solid content is 30 wt %).
[0081] Comparative Example 2
[0082] The only difference from Example 2 is that the content of trichloroethane in the mixed system is 70 wt % (ie, the solid content is 30 wt %).
[0083] Comparative Example 3
[0084] The only difference from Example 3 is that the content of trichloroethane in the mixed system is 70 wt % (ie, the solid content is 30 wt %).
[0085] Comparative Example 4
[0086] The only difference from Example 4 is that the content of trichloroethane in the mixed system is 70 wt % (ie, the solid content is 30 wt %).
[0087] Characterization and testing
[0088] 1) Figure 1 It is the infrared image of different substances in Example 1, wherein a is the infrared image of the raw materials used for synthesizing co-crystallized polyurethane, and b is the infrared image of the raw materials used for synthesizing co-crystallized polyurethane and the product co-crystallized polyurethane. In a, PPDLDA (poly (ω-pentadecalactone) diallyl formamide) and PCLDA (poly (ε-caprolactone) diallyl formamide) have double bond peaks (compared with diol monomers (poly (ω-pentadecalactone) diol and poly (ε-caprolactone) diol)), and the isocyanate group disappears (compared with allyl isocyanate), indicating that PPDLDA and PCLDA are successfully prepared. In b, the reduction of the double bond peak in the cross-linked polymer (compared with PPDLDA and PCLDA) and the disappearance of the sulfhydryl group (compared with the cross-linking agent TMPMP) prove that the polyurethane is successfully prepared.
[0089] 2) Figure 2 The DSC curve of the bidirectional shape memory co-crystallized polyurethane obtained by photocuring at a high solvent content in Example 1 is shown in FIG. Figure 2 As shown, the prepared polyurethane has two crystallization transitions and three melting transitions. The left melting transition is the crystallization of PCL, the existence of the middle melting transition is the co-crystallization of PCL and PPDL, and the existence of the right melting transition is due to the crystallization of PPDL. That is, there are three melting transitions and two crystallization transitions, and the results of Examples 2 to 4 are similar.
[0090] 3) The shape memory cycle curve is obtained under DMA850. The specific temperature parameter is selected as T p =100℃, T high =60℃, 70℃, 80℃. T low =0℃. Implementation process: The temperature is raised to 100℃, and the heating rate is 5℃ / min. The sample is at T p (100℃)(maintained for 10min) stretched to 150% strain. Cooled to 0℃, cooling rate 5℃ / min, and maintained for 10min; then the stress on the sample was removed and the temperature was kept at 0℃ for 10min. The sample was reheated to T high (60℃)(Under no stress), keep warm for 10min, and then cool to T low (0℃)(Under no stress), keep warm for 10min, and heat up and down at a rate of 5℃ / min. high -T low Repeat the above heating and cooling cycle. Every three cycles T highIncrease 10℃. That is, the sample is repeated three times at 0-60-0℃, 0-70-0℃, and 0-80-0℃. low The sample strain at time is recorded as ε1, T high The sample strain is recorded as ε2. Then the reversible strain of the sample is ε1-ε2.
[0091] Figure 3 The two-way shape memory performance test results of the two-way shape memory co-crystallized polyurethane obtained by photocuring at a high solvent content in Example 1 (the solid line is strain, the dashed line is temperature, and the dot-dash line is stress). p =100℃, T low = 0℃ unchanged. Statistics T high Reversible strain at 60℃, 70℃ and 80℃. Figure 3 As shown, each T high ε1 and T low The ε2 at that time is subtracted and recorded as T high The reversible strain at 50° is shown in Table 1.
[0092] 4) Figure 4 The DSC curve of the bidirectional shape memory polyurethane prepared by curing at low solvent content in Comparative Example 1 is shown in FIG. Figure 4 It can be seen that compared with Examples 1 to 4, it has 2 melting transitions and 2 crystallization transitions, which are only derived from the phase separation of the PCL / PPDL system. There is no new melting transition caused by co-crystallization. The results of Comparative Examples 2 to 4 are similar.
[0093] 5) Figure 5 The two-way shape memory performance test results of the two-way shape memory polyurethane prepared by curing at a low solvent content in Comparative Example 1 (solid line is strain, dashed line is temperature, and dot-dash line is stress). p =100℃, T low = 0℃ unchanged. Statistics T high Reversible strain at 60℃, 70℃ and 80℃. Figure 5 As shown, each T high ε1 and T low The ε2 at that time is subtracted and recorded as T high The reversible strain at 50° is shown in Table 1.
[0094] 6) Figure 6 This is a diagram showing the quadruple shape memory performance of the co-crystallized polyurethane obtained by curing at a high solvent content in Example 1. Figure 6 As shown, the long strip material ( Figure 6 S1) is deformed at 100°C and fixed at 80°C to obtain a shape such as Figure 6 As shown in S2; deformed again at 80℃, fixed at 40℃ to obtain the shape as shown in Figure 6As shown in S3; deformed again at 40℃, and fixed at 0℃ to obtain the shape as shown in Figure 6 Then it is heated to 40℃, and the deformed shape is restored to a certain extent at this temperature, as shown in S4. Figure 6 As shown in S5; when heated to 80 ° C, the shape previously deformed at this temperature is restored, as shown in Figure 6 As shown in S6; when heated to 100°C, the material returns to its initial long strip shape ( Figure 6 S1). Examples 2 to 4 have co-crystallization properties and all have two crystallization transitions and three melting transitions, and their effects are similar.
[0095] Table 1 Average modulus and different T values of polyurethanes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 high Reversible strain data
[0096]
[0097]
[0098] As shown in Table 1, the nanomechanical strength of the bidirectional shape memory co-crystallized polyurethane prepared by curing at a high solvent content in Examples 1 to 4 is higher than that of the samples cured at a low solvent content in Comparative Examples 1 to 4. high Under the above conditions, the reversible strain of the two-way shape memory co-crystallized polyurethane materials obtained by curing in Examples 1 to 4 at high solvent content is greater than that of the samples obtained by curing in Comparative Examples 1 to 4 at low solvent content. Compared with the control samples of Comparative Examples 1 to 4 at low solvent content, the reversible strain of the co-crystallized polyurethane increases with T high The increase in high When the temperature increases from 60℃ to 70℃). high When the temperature is increased to 80°C, the co-crystallized polyurethane still has reversible strain. The above results all indicate that, compared with low solvent content curing, the bidirectional shape memory co-crystallized polyurethane obtained by the present invention at high solvent content curing has improved nanomechanical properties, increased reversible strain, and enhanced temperature resistance of bidirectional shape memory performance.
[0099] In the case of a large amount of solvent, the photocuring of Examples 1 to 4 was gel, and after the solvent was removed, the PCL segment and the PPDL segment could co-crystallize, and the co-crystallized samples had an advantage in shape memory performance. However, in Comparative Examples 1 to 4, the photocuring in a small amount of solvent did not have co-crystallization and no shape memory advantage.
[0100] It can be seen from the above embodiments and comparative examples that the system exhibits 3 melting transitions and 2 crystallization transitions under high solvent content curing, while the material exhibits only 2 melting transitions and two crystallization transitions under low solvent content curing. Low solvent content curing originates from the phase separation of PCL and PPDL in the polymer; high solvent content curing includes PCL / PPDL co-crystallization in addition to phase separation, and thus exhibits the thermodynamic property of an additional melting transition. Compared with the polyurethane material cured under low solvent content (solvent content of 70wt%), the more evenly dispersed PPDL and the co-crystallization properties of the system under high solvent content (85-92wt%) also improve the nanomechanical properties of this system (average modulus measured by AFM), enhance the temperature resistance of the two-way shape memory property, and have a larger reversible strain. The presence of 3 melting transitions and two crystallization transitions under high melting transition makes the material exhibit quadruple shape memory properties.
[0101] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a quadruple-reversible shape memory co-crystallized polyurethane, characterized in that: The following steps are involved: The method comprises mixing poly(ω-pentadecalactone) diallylformamide, a double-bond-terminated poly(ε-caprolactone) compound, a trithiol crosslinking agent, a photoinitiator and an organic solvent, photocuring the obtained mixed system, and removing the solvent to obtain a quadruple-reversible shape memory co-crystalline polyurethane; wherein the mass fraction of the organic solvent in the mixed system is 85-92wt%; The double-bond terminated poly(ε-caprolactone) compounds include poly(ε-caprolactone) diallylformamide or poly(ε-caprolactone) diacrylate.
2. The preparation method according to claim 1, characterized in that: The preparation method of the poly(ω-pentadecalactone) diallylformamide comprises the following steps: Poly(ω-pentadecalactone) diol, allyl isocyanate, a catalyst and a first solvent are mixed to carry out a first addition reaction to obtain poly(ω-pentadecalactone) diallylformamide; the molar ratio of the poly(ω-pentadecalactone) diol to allyl isocyanate is 1:(2-3); the catalyst is dibutyltin dilaurate, and the mass of the catalyst is 1-4% of the mass of the poly(ω-pentadecalactone) diol; the temperature of the first addition reaction is 85-95°C, and the time is 5h.
3. The preparation method according to claim 2, characterized in that: The preparation method of the poly(ω-pentadecalactone) diol comprises the following steps: 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, 1,8-octanediol and ω-pentadecalactone are mixed, and the obtained mixture is subjected to a ring-opening polymerization reaction to obtain poly(ω-pentadecalactone)diol; the mass of the 1,5,7-triazidobicyclo(4.4.0)dec-5-ene is 1 to 3.5% of the mass of the mixture; the mass of the 1,8-octanediol is 2 to 3.5% of the mass of the mixture; the temperature of the ring-opening polymerization reaction is 100°C and the time is 48 hours.
4. The preparation method according to claim 1, characterized in that: The preparation method of the poly(ε-caprolactone) diallylformamide comprises the following steps: Poly(ε-caprolactone) diol, allyl isocyanate, a catalyst and a second solvent are mixed to carry out a second addition reaction to obtain poly(ε-caprolactone) diallyl formamide; the molar ratio of the poly(ε-caprolactone) diol to allyl isocyanate is 1:(2-3); the catalyst is dibutyltin dilaurate, and the mass of the catalyst is 0.5-2% of the mass of the poly(ε-caprolactone) diol; the temperature of the second addition reaction is 85-95°C and the time is 5h.
5. The preparation method according to claim 1, 2 or 4, characterized in that: The mass of the poly(ω-pentadecalactone) diallyl formamide is 5-20% of the sum of the masses of the poly(ω-pentadecalactone) diallyl formamide and the poly(ε-caprolactone) compound.
6. The preparation method according to claim 1, characterized in that: The organic solvent includes trichloroethane or chloroform, and the solid content of the mixed system is 8 to 15 wt %; the trithiol crosslinking agent includes trimethylolpropane tris(3-mercaptopropionate); the molar ratio of the thiol group in the trithiol crosslinking agent to the total double bond functional groups in the double-bond terminated poly(ε-caprolactone) compounds and poly(ω-pentadecalactone) diallylformamide) is 3:(2 to 6).
7. The preparation method according to claim 1, characterized in that: The photoinitiator includes a photoinitiator 651; the mass of the photoinitiator is 1-5% of the sum of the mass of the poly(ω-pentadecalactone) diallylformamide and the poly(ε-caprolactone) compound.
8. The preparation method according to claim 1, characterized in that: The light curing time is 5 to 10 minutes.
9. The quadruple-reversible shape memory co-crystalline polyurethane prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the quadruple-reversible shape memory co-crystallized polyurethane according to claim 9 in intelligent control, biomedical intelligent materials or soft robots.
Citation Information
Patent Citations
Preparation method of reshapeable shape memory elastomer based on eutectic crystal
CN111269373A
Bidirectional shape-memory polymer, method of its production and its use
US20150344600A1